ASSESSMENT OF YIELD PER UNIT GLOBAL WARMING POTENTIAL (GWP) OF CONTROLLED ENVIRONMENTAL AGRICULTURE (CEA) AND FIELD-BASED CHILLI PEPPER PRODUCTION IN NORTHWESTERN, NIGERIA - Ayinde, T.B. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This study evaluates the performance metrics of chilli pepper production using Controlled Environment Agriculture (CEA), rainfed field, and irrigated field methods in Likoro, Kudan LGA of Kaduna State. We use life cycle inventory (LCI) methods to estimate total fixed and variable costs, yield, saleable product, price, total revenue, gain from investment, return on investment (ROI), and global warming potential (GWP). CEA incurs the highest total cost of production at ₦4,222,893/ha but yields significantly more (72,000 kg/ha/year) compared to rainfed (900 kg/ha/year) and irrigated fields (4,500 kg/ha/year). The saleable product for CEA is 68,400 kg/ha/year, while rainfed and irrigated fields produce 360 kg/ha/year and 3,825 kg/ha/year, respectively. The total revenue generated by CEA is ₦47,880,000, with a gain from investment of ₦47,457,711, and an impressive ROI of 1,124%. In contrast, rainfed fields produce a total revenue of ₦360,000, with a gain from investment of ₦309,105, and an ROI of 61%. Irrigated fields generate a total revenue of ₦1,530,000, with a gain from investment of ₦1,361,596, and an ROI of 81%. The GWP is lowest for CEA at 0.03 CO2eq/kg, whereas rainfed and irrigated fields have higher GWP values of 445.26 CO2eq/kg and 42.21 CO2eq/kg, respectively. The findings highlight CEA offers a sustainable alternative to traditional field-based methods, with higher ROI(1,124%) and lower greenhouse gas emissions (0.03 CO2eq/kg). This highlights CEA's efficiency and sustainability, making it an attractive option for environmentally conscious and economically viable farmers.